2018
DOI: 10.1002/jcp.27863
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MUC1‐C regulates metabolism by AKT pathway in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common digestive tumors worldwide. The Mucin 1 (MUC1) heterodimeric protein has been confirmed that is overexpressed in ESCC and induced adverse outcomes. However, the detailed mechanism(s) remained challenging. So, we investigated the relationship between MUC1‐C and metabolism in ESCC cells. In the results, TP53‐induced glycolysis and apoptosis regulator (TIGAR) was overexpressed and correlative with MUC1‐C positively in ESCC tissue. Targeting MUC1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…Previous studies have shown that overexpression of MUC1 leads to the upregulation of signaling molecules involved in PI3K/Akt/mTOR pathway. Genetical depletion or drug inhibition of MUC1 would otherwise inhibit signal transduction of PI3K/Akt/mTOR [40,41]. Our study showed that MUC1 overexpression promoted the activation of PI3K/Akt, which was consistent with previous results.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that overexpression of MUC1 leads to the upregulation of signaling molecules involved in PI3K/Akt/mTOR pathway. Genetical depletion or drug inhibition of MUC1 would otherwise inhibit signal transduction of PI3K/Akt/mTOR [40,41]. Our study showed that MUC1 overexpression promoted the activation of PI3K/Akt, which was consistent with previous results.…”
Section: Discussionsupporting
confidence: 93%
“…GO‐203 blocks this CQC motif, and inhibits the function of MUC1‐C as an intracellular signaling protein 30 . GO‐203 was shown previously to be effective at inhibiting cell proliferation in an in vitro assay and in xenograft models of breast, esophageal, lung, and colorectal carcinomas 31‐34 . The present study demonstrated that the targeting of MUC1‐C with GO‐203 inhibited p‐AKT in UC cells, which suppressed the downstream target, MDR1.…”
Section: Discussionsupporting
confidence: 61%
“…GO-201 was shown to be effective against human prostate, breast, pancreatic and esophageal squamous cell carcinoma tumor xenograft models at different dosedependent schedules, whereas CP-1 had no apparent effect on tumor growth or histology 30,41,45,46 . GO-201 and GO-203 both contain the CQCRRKN sequence, block MUC1-C dimerization and have similar dose-dependent activity in vitro and in vivo 28,42,47,48 . In addition, treatment of tumors with GO-203 encapsulated in nanoparticles (GO-203/NPs) has demonstrated dose-dependent activity 49 .…”
Section: Muc1-c Drives Pathways Associated With Lineage Plasticitymentioning
confidence: 99%